New chemical analogs of triglycine sulfate - Ghazaryan, V.V.; Fleck, M.; Petrosyan, A.M. (Journal of crystal growth, 2014)
Triglycine sulfate (TGS) and its analogs can be presented by the molecular structure AH(A⋯AH)Y, where A is an amino acid (glycine in TGS) in zwitter-ionic form, AH is a protonated cationic amino acid, (A⋯AH) is a dimeric cation, where A and AH are connected by a short hydrogen bond, and Y is a divalent anion. Doing research on amino acid hexafluorosilicates we obtained a series of salts with different compositions, including four hexafluorosilicate salts which chemically are analogs of triglycine sulfate. Those are GlyH(Gly⋯GlyH)SiF6 (I), SarH(Sar⋯SarH)SiF6·2H2O (II), l-AlaH(l-Ala⋯l-AlaH)SiF6·H2O (III) and l-ProH(l-Pro⋯l-ProH)SiF6·H2O (IV). We have already published our results on crystals (II) and (III). In this work we report our results on the crystals (I) and (IV). •We found four amino acid hexafluorosilicate salts in 3:1 compositions.•These salts are chemical analogs of triglycine sulfate.•Crystals and molecular structures are given.